Exploring the Potential Mechanisms of Action of the Mindfulness-based Social Work and Self-care Programme. (9th April 2022) - Maddock, Alan; McCusker, Pearse
Abstract: The mindfulness-based social work and self-care (MBSWSC) programme was created in order to support social work students and practitioners to develop enhanced social work and self-care skills. This programme was found to improve feelings of stress, anxiety, mental well-being and burnout of thirty social work students. An explanatory sequential mixed methods design was chosen in order to generate a comprehensive understanding of what the potential mechanisms of action of MBSWSC might be. Data were collected using validated quantitative measures and through an open-ended qualitative questionnaire. The quantitative data were analysed using regression analyses. The qualitative data were thematically analysed. Though this study contains limitations, it's results suggest that social work student stress, feelings of burnout, anxiety and wellbeing can be improved by supporting students to develop approach-oriented stress coping skills and capacities in acceptance, mindfulness, self-compassion, non-attachment, attention regulation/decentering and non-aversion. This study suggests that these skills and capacities can work individually or collectively to directly improve these outcomes and also indirectly by reducing a student's tendency to think negatively when they are stressed. The results provide some preliminary evidence on what the mechanisms of MBSWSC might be, enhancing our understanding of how mindfulness-based programmes might achieve positive outcomes. Abstract : Social work students can experience high levels of stress, burnout along with mental health and well-being deficits during their training. In order to support social work students to cope with the demands of their education, the mindfulness-based social work and self-care programme (MBSWSC) programme was developed. This programme was piloted with social work students and was found to improve social work student stress, feelings of burnout, their mental health and well-being. A number of other important mindfulness skills, for example self-compassion, were also found to improve due to the student's participation in the MBSWSC programme. This mixed methods study explored if changes in these skills might help to explain the changes in social work student stress, feelings of burnout, their mental health and well-being. This study found evidence on why social work student stress, feelings of burnout, mental health and well-being might have changed after the participants completed MBSWSC programme. These findings help us to understand more about how the MBSWSC and other mindfulness-based programmes might work.